Pengaruh Waktu dan Konsentrasi Paclobutrazol Terhadap Pertumbuhan Bunga Matahari (Hellianthus annuus L.) - Egith Marshel; Mbue Kata Bangun; Lollie Agustina P Putri (Universitas Sumatera Utara, 2015)
The research aimed to know the influence by the time of application and concentration of paclobutrazol to growth of Sunflower. The research was carried out in the gauze house, Agricultural Faculty of North Sumatera University from September 2013 to January 2014. This research used Split Plot Design with two factors. Main plot was time of application of paclobutrazol consist of three levels: 3 weeks after planting (WAP);4 WAP; 5 WAP. Sub plot was Paclobutrazol concentration consist of four levels are 0 ppm; 50 ppm; 100 ppm; 150 ppm. The parameters in this research were plant height, number of leaf, stem diameter and root length.The results showed that time of application of paclobutrazol has no effect significantly yet to all parameters. Paclobutrazol concentration give effect significantly to plant height and stem diameter on 6 WAP until 11 WAP. While interaction between time of application and concentration of paclobutrazol have no effect significantly yet to all parameters.Keywords: paclobutrazol, sunflower, time of application